CpG-containing immunostimulatory DNA sequences elicit TNF-α–dependent toxicity in rodents but not in humans - John D. Campbell; Yan Cho; Martyn L. Foster; Holger Kanzler; Melissa A. Kachura; Jeremy A. Lum; Marianne J. Ratcliffe; Atul Sathe; Andrew J. Leishman; Ash Bahl; Mark McHale; Robert L. Coffman; et al. (The Journal of Clinical Investigation, 2009)
CpG-containing immunostimulatory DNA sequences (ISS), which signal through TLR9, are being developed as a therapy for allergic indications and have proven to be safe and well tolerated in humans when administrated via the pulmonary route. In contrast, ISS inhalation has unexplained toxicity in rodents, which express TLR9 in monocyte/macrophage lineage cells as well as in plasmacytoid DCs (pDCs) and B cells, the principal TLR9-expressing cells in humans. We therefore investigated the mechanisms underlying this rodent-specific toxicity and its implications for humans. Mice responded to intranasally administered 1018 ISS, a representative B class ISS, with strictly TLR9-dependent toxicity, including lung inflammation and weight loss, that was fully reversible and pDC and B cell independent. Knockout mouse experiments demonstrated that ISS-induced toxicity was critically dependent on TNF-α, with IFN-α required for TNF-α induction. In contrast, human PBMCs, human alveolar macrophages, and airway-derived cells from Ascaris suum–allergic cynomolgus monkeys did not produce appreciable TNF-α in vitro in response to ISS stimulation. Moreover, sputum of allergic humans exposed to inhaled ISS demonstrated induction of IFN-inducible genes but minimal TNF-α induction. These data demonstrate that ISS induce rodent-specific TNF-α–dependent toxicity that is absent in humans and reflective of differential TLR9 expression patterns in rodents versus humans.